MINYAK KELAPA HASIL FERMENTASI MENGGUNAKAN RAGI TAPE DENGAN KONSENTRASI DAN LAMA FERMENTASI YANG BERVARIASI - Uswatun Hasanah (JURNAL KELUARGA SEHAT SEJAHTERA, 2013)
ABSTRACT This study is aimed at finding out the effect of concentration of yeast and fermentation time on the results of coconut oil. The study design was a complete random design (CRD) with factorial with two factors: the yeast concentration consists of five levels and fermentation time factor of five levels. The study was conducted with two repetitions. The results showed that coconut oil has the highest results obtained from the treatment concentration of 15 grams of yeast and fermentation time 24 -hour treatment is respectively 29.34% and 29.38%. Highest oil yields were also obtained from the interaction treatment concentration of 15 grams of yeast and fermentation time 24 hours is 35.44%. Kata Kunci : Minyak kelapa, fermentasi, ragi tape.